A mechanism linking ferroptosis and ferritinophagy in melatonin-related improvement of diabetic brain injury - Jiaojiao Yu; Yu Zhang; Qin Zhu; Zhengrui Ren; Mengting Wang; Sasa Kong; Hongbo Lv; Tao Xu; Zhaoyu Xie; Han Meng; Jun Han; Hui Che (iScience, 2024)
Summary: Ferroptosis and ferritinophagy play critical roles in various disease contexts. Herein, we observed that ferroptosis and ferritinophagy were induced both in the brains of mice with diabetes mellitus (DM) and neuronal cells after high glucose (HG) treatment, as evidenced by decreases in GPX4, SLC7A11, and ferritin levels, but increases in NCOA4 levels. Interestingly, melatonin administration ameliorated neuronal damage by inhibiting ferroptosis and ferritinophagy both in vivo and in vitro. At the molecular level, we found that not only the ferroptosis inducer p53 but also the ferritinophagy mediator NCOA4 was the potential target of miR-214-3p, which was downregulated by DM status or HG insult, but was increased after melatonin treatment. However, the inhibitory effects of melatonin on ferroptosis and ferritinophagy were blocked by miR-214-3p downregulation. These findings suggest that melatonin is a potential drug for improving diabetic brain damage by inhibiting p53-mediated ferroptosis and NCOA4-mediated ferritinophagy through regulating miR-214-3p in neurons.